Impact of aspirin on bleeding and blood product usage in off‐pump and on‐pump coronary artery bypass graft surgery. Issue 2 (16th February 2022) - Little, Christopher; Odho, Zain; Szydlo, Richard; Aw, Tuan‐Chen; Laffan, Mike; Arachchillage, Deepa R. J.
Abstract: Major bleeding is linked to poorer outcomes following cardiac surgery. Current guidelines recommend continuation of aspirin prior to coronary artery by‐pass graft (CABG) but the effect of continuing aspirin in patients with prior indication for aspirin, in particular during off‐pump CABG (OPCABG), has not been systematically assessed. In this study, we analysed the effect of continuing aspirin prior to OPCABG and on‐pump CABG with respect to bleeding and blood product usage. We compared propensity‐matched cohorts of patients who continued aspirin until the day of OPCABG or CABG to controls (no antiplatelet) and to patients discontinuing aspirin 5–7 days prior. Length of hospital stay, 30‐day mortality and thromboembolism rates were similar for both OPCABG and CABG. During OPCABG, aspirin‐continued patients received more intraoperative red cell units compared to controls without difference in bleeding. Aspirin‐continued patients received more blood products perioperatively and bled more than aspirin‐discontinued patients undergoing OPCABG. The only difference during CABG was a small increase in the volume of cells salvaged among aspirin‐continued patients compared to controls. Current guidelines on the continuation of aspirin prior to CABG and OPCABG are safe. Continuation of aspirin prior to OPCABG may result in more bleeding and blood product usage.